DINAMIKA INTEGRASI SOSIAL DI PAPUA FENOMENA MASYARAKAT FAKFAK DI PROVINSI PAPUA BARAT - Saidin Ernas (Universitas Gadjah Mada, 2014)
This paper aims to explain that the social dynamics in Papua does not always present the story ofconflict and disintegration, but also about the social integration, harmony, and peace as can be observedin the Fakfak community in West Papua Province. By using the methods of descriptive analysis of thequalitative data collected from field observations, interviews and documentation studies, the authorsmanaged to formulate several important findings. First, the results of acculturation between religiousvalues and culture are important elements that make the social norms of harmonious and tolerant inFakfak, as described in the local knowledge of “the three furnaces stone”. Second, the institutionalizationof values and social integration processes in the community can work well, if the support of local forcesand civil society groups work together to promote peace. At the same time, this paper also reminds thatthe conflict issues, such as religious radicalism and separatism, if not handled carefully can potentiallydamage the social integration that has been well maintained.